Prevalence of exclusive breastfeeding practice in the first six months of life and its determinants in Iran: a systematic review and meta-analysis - Meysam Behzadifar; Mandana Saki; Masoud Behzadifar; Mahnaz Mardani; Fatemeh Yari; Farzad Ebrahimzadeh; Hadis Majidi Mehr; Shadi Abdi Bastami; Nicola Luigi Bragazzi (BMC, 2019)
Abstract Background Exclusive breastfeeding (EBF) in the first 6 months of life is the best and most complete option for an infant, in that supplies the vitamins and minerals the baby needs. Several studies in Iran have been conducted concerning the prevalence of EBF. The aim of this study was to determine the prevalence of EBF in the first 6 months of life and associated factors in Iran synthesizing published studies. Methods We searched PubMed/MEDLINE, Embase, Scopus, ISI/Web of Science, the Cochrane Library, Directory of Open Access Journals Directory (DOAJ) and Google Scholar as well as Iranian databases (Barakathns, MagIran and the Scientific Information Database or SID) up to November 2018. The Newcastle-Ottawa Scale was used to assess the quality of studies. Analyses were performed by pooling together studies using DerSimonian-Laird random-effects model with 95% confidence interval. To test for heterogeneity, I2 test was used. The Egger's regression test and funnel plot were used to evaluate the publication bias. The strength of EBF determinants was assessed computing the Odds-ratios (OR) using the Mantel-Haenszel method. Results In the initial search 725 records were found. Finally, 32 studies were selected based on inclusion/exclusion criteria. The sample size of studies varied between 50 and 63,071 subjects. The overall prevalence of EBF in Iran was 53% (CI 95%; 44-62). The OR for breastfeeding education received before pregnancy was 1.13 (0.94-1.36), for mother's job 1.01 (0.81-1.27), for education level 1.12 (0.89-1.42), for type of delivery 1.16 (0.98-1.37), and for gender of child 1.03 (0.83-1.28). Conclusion In Iran health policy- and decision-makers should try to take interventions that encourage mothers to use their milk to breastfeed the infants.